Thermal and Stress-Strain State of Cast Bodies of Control Valves of 200 MW Power Units - Chernousenko, O. Yu.; Ryndiuk, Dmytro V.; Peshko, Vitalii A. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2020)
200 MW steam turbines of DTEK Lugansk TPP units have operated for about 305–330 thousand hours with a total number of starts from 1.438 to 1,704, as of the end of 2019. The term for extending the operation of high-temperature power equipment between scheduled preventive maintenances has expired. When extending the operation of cylinder bodies and rotors, one should also pay attention to steam distribution elements. A peculiarity of the re-extension of the operation of a 200 MW power unit is the beyond-design operating time of power equipment of more than 250 thousand hours and the operation of equipment in maneuverable modes (more than 1,700 starts from various thermal states), with covering peaks of the electrical load with the excess of the number of starts for certain types of equipment by two to three times. Such a significant number of variable operating modes negatively affects the life cycle of equipment and requires studying the influence of the main damage mechanisms on the metal of cast components. The paper presents a calculated study of the thermal and stress-strain states of high- pressure (HP) and intermediate-pressure (IP) control valves of a K-200-130 turbine. The calculations were carried out using three-dimensional geometric models, as well as taking into account real operating conditions. The geometric model of HP control-valve bodies was constructed taking into account the complex geometry during the transition from the inlet nozzles to the valve vapor volume with a subsequent narrowing of the outlet nozzle section to the control stage of the HP cylinder. Similarly, the geometric model of IP control-valve bodies was constructed taking into account the complex spatial geometry according to the drawings provided by the operating organization. A numerical study of the thermal and stress-strain states was carried out for typical operating modes, using the finite element method. Start-up modes were investigated in a non-stationary setting, while constant ones – in a stationary setting. The thermal states of HP and IP control valves were calculated for three variants of startup modes: cold-startup mode at an initial metal temperature of 100 °C, warm-startup mode at an initial metal temperature of 250 °C, and hot-startup mode at an initial metal temperature of 410 °C. The boundary conditions for thermal state calculations were determined using real and most representative startup schedules provided by the power plant. When calculating thermal states for different startup modes, the dynamics of changes in temperature gradients was taken into consideration. During the stress-strain state studies, the main zones of stress concentration in control valves of a K-200-130 steam turbine were established.